2021
DOI: 10.3390/agronomy11071283
|View full text |Cite
|
Sign up to set email alerts
|

Drought and Salinity in Citriculture: Optimal Practices to Alleviate Salinity and Water Stress

Abstract: Among the various abiotic stresses, drought is the major factor limiting crop productivity worldwide. Citrus has been recognized as a fruit tree crop group of great importance to the global agricultural sector since there are 140 citrus-producing countries worldwide. The majority of citrus-producing areas are subjected to dry and hot summer weather, limited availability of water resources with parallel low-quality irrigation water due to increased salinity regimes. Citrus trees are generally classified as “sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 98 publications
0
31
0
2
Order By: Relevance
“…On the other hand, Ziogas et al (2021) suggest that increasing water content in the leaf promotes the dilution of ions within the cells, which allows the presence of salts at high concentrations in parts of the tissues without causing damage to the cells. In other words, the increase in leaf succulence, which is the water content per unit area, is an indication of osmotic adjustment.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, Ziogas et al (2021) suggest that increasing water content in the leaf promotes the dilution of ions within the cells, which allows the presence of salts at high concentrations in parts of the tissues without causing damage to the cells. In other words, the increase in leaf succulence, which is the water content per unit area, is an indication of osmotic adjustment.…”
Section: Resultsmentioning
confidence: 99%
“…Although in the present study, no obvious shoot growth and shoot abundance were found across the water deficit treatments. In general, water stress or water deficit can reduce nonstructural sugar content, canopy growth and yield in citrus (Pérez‐Pérez et al, 2008; Ziogas et al, 2021). However, some drought‐tolerant citrus rootstocks can alleviate the negative effect of drought on plant growth, for example maintaining canopy growth (Sampaio et al, 2021) and induced root growth (Pedroso et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Drought, or, in other words, limited access to water is considered one of the most limiting citrus growth and production factors with adverse effects. This stress negatively affects citrus production and will be progressively more intense in some areas due to global climate changes [15,16]. Climate change event and, consequently, global warming has exacerbated the destructive effects of drought stress with various impacts on temperature and rainfall patterns in different areas [10].…”
Section: Drought Stress and Its Management And Mitigation Strategiesmentioning
confidence: 99%